Third-generation antipsychotics in patients with schizophrenia and non-responsivity or intolerance to clozapine regimen: What is the evidence? - Vasiliu, Octavian (Frontiers in Psychiatry, 2022)
Clozapine is considered « the golden standard » for the management of treatment-resistant schizophrenia, but many patients do not present adequate responsivity even to this antipsychotic. If we add the need to strictly monitor the hematologic and cardiometabolic adverse events during each clozapine trial and the difficulty of preserving therapeutic adherence in patients with low insight, residual negative/positive symptoms, or economic challenges, then the necessity of exploring alternative interventions for these patients becomes obvious. Also, in case of intolerance to clozapine, or where clozapine did not induce remission, the clinicians have to find new ways to help their patients. Switching to other antipsychotics or using these agents as add-ons to clozapine are the main interventions explored in this review, for patients with schizophrenia resistant to clozapine (ultra-resistant schizophrenia, URS). When clozapine intolerance is detected, conversion to another antipsychotic with distinct pharmacologic properties or formulation (e.g., long-acting intramuscular injectable agents, LAI) may be a useful option. This narrative review is based on searching in four electronic databases, that retrieved 19 primary and secondary reports on aripiprazole (seven case reports or case series presenting 24 patients; nine clinical trials, and three systematic reviews/meta-analyses), two primary reports on brexpiprazole (case report and case series, N=3 patients), and six primary reports on cariprazine (case reports and case series, N=14 patients). Based on the information collected from these reports, which included oral and LAI formulations, the TGA most supported by evidence for the augmentation of clozapine is aripiprazole (high- and medium-quality data), followed by cariprazine (low-quality data). Brexpiprazole has not yet been systematically explored for this indication, and in the case of lumateperone, no report could be found. The efficacy of aripiprazole and cariprazine was supported in the domains of positive, negative, and general symptoms, and aripiprazole may positively impact the metabolic profile in patients with URS. Also, adding TGA may lead to a decrease in the dose of clozapine concomitantly administered. More data derived from good quality research are needed in order to confirm the circumstances of TGAs recommendation in patients with URS, either as monotherapy, or added to clozapine.